Influence of Scientific and Technical Progress on Change Management in Business and Education ("Journal "U". Economy. Management. Finance.", 2017)
The problem of scientific and technical progress influence on spheres of business and education, and also on their interaction is revealed in the article. Dynamics of development of management as a field of knowledge and professional activity is described. Technological tendencies, their influence on labor market and functioning of the organizations in the present and the future are analyzed.
Keywords: the relevance of professions; change management; scientific and technical progress; business and education; enterprises and universities; the turquoise of the organization